A Study on The Role of Artficials Intelligence In Managing Physical Distribution Of Medicines In Pharmaceutical Industry During Covid–19 Pandemic (Journal of Finance, Business and Management Studies, 2022)
Supply chain management of goods or service means the entire manufacturing flow, starting from the raw components procurement to providing finished product to the customer. It enhances the smooth flow of products in reaching the market and helps the customers to get an easy access to all the essential products like food, clothing and drugs at the right time and right place. Among all the basic amenities, it is drugs that demands the quick process of delivery. It is promoted by the pharmaceutical supply chain which assists in the manufacturing and meticulous delivery of medicines to patient. Physical distribution of medicine has become an impossible task in this pandemic which called for an immediate urge for the use of Artificial Intelligence (AI) in medicine distribution. Artificial Intelligence is the stimulation of human intelligence processes by machines, especially through computer systems. Use of AI in distribution of medicine proves to be more effective in this lockdown. This paper explores the role of Artificial Intelligence in managing physical distribution of medicines in pharmaceutical industry. Effective physical distribution is an integral part of Supply Chain which is intensified with the use of AI. Specific applications of AI include expert systems, natural language processing, speech recognition and machine version. The usage of AI in physical distribution of drugs has increased the efficiency in the complete process of physical flow of medicines from the pharmacy to the patients and delivering the medicines at the right time. Thus, this paper gives a conceptual idea regarding how the functions of AI supports in managing physical distribution of medicine in pharmaceutical industry.
Keywords: Artificial Intelligence; Supply Chain; Pharmaceutical industry; Pandemic